1975
DOI: 10.1113/expphysiol.1975.sp002321
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Metabolism of the Shivering Hind Leg of the Young Ox During Several Days of Continuous Cold Exposure

Abstract: The effect of 4 days of continuous exposure to a cold environment on blood flow in, and oxygen and energy substrate uptake by the shivering hind leg has been studied in young steers. The animals shivered throughout the period of cold exposure and total oxygen consumption (total V0o) remained 40-50% greater than Vo, during thermoneutrality. Leg blood flow (leg 0) and oxygen uptake (leg Vo,) increased two-and four-fold respectively on the first day of cold. Both had declined significantly by the final day, leg Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

1976
1976
1990
1990

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
2
1
0
Order By: Relevance
“…The detection of an increased blood flow during cold exposure is therefore all the more notable and it seems likely that an even greater response would have been obtained if only the subcutaneous and intermuscular depots had been considered. This increase is consistent with the apparent increase in the rate of lipolysis in bovine leg adipose tissue during cold exposure (Bell et al 1975), although during noradrenaline infusion, at least, lipolysis and vasodilatation in adipose tissue are not necessarily directly related (Mjos & Akre, 1971).…”
Section: Tissue Blood Flow In the Bovine Hind Leg 241supporting
confidence: 82%
See 1 more Smart Citation
“…The detection of an increased blood flow during cold exposure is therefore all the more notable and it seems likely that an even greater response would have been obtained if only the subcutaneous and intermuscular depots had been considered. This increase is consistent with the apparent increase in the rate of lipolysis in bovine leg adipose tissue during cold exposure (Bell et al 1975), although during noradrenaline infusion, at least, lipolysis and vasodilatation in adipose tissue are not necessarily directly related (Mjos & Akre, 1971).…”
Section: Tissue Blood Flow In the Bovine Hind Leg 241supporting
confidence: 82%
“…For this reason, and because of its surgical accessibility, the hind limb has been extensively used in this laboratory as a means of studying the metabolism of shivering muscle in vivo in the conscious ox (e.g. Bell et al 1975). However, dissection of hind limbs from the young steers used in these experiments showed that almost 40 % of the limb consists of the non-muscular tissues bone, skin, connective tissue and fat.…”
Section: Introductionmentioning
confidence: 99%
“…However, liver glycogen reserves could not support the observed rate of glucose release for more than several hours. The sustained elevation in glucose production and utilization during more prolonged cold exposure of sheep [McKay et al, 1974] and young cattle [Bell, Clarke and Thompson, 1975] must therefore be associated with a substantially increased rate of gluconeogenesis, because little glucose is of directly dietary origin in the normally-fed ruminant [Leng, 1970]. The present results and those of Thompson et al [1975] for hepatic uptake of non-hexose glucose precursors, in sheep exposed to cold for several hours, support this contention.…”
supporting
confidence: 63%